The Effect of Phacoemulsification Surgery on Corneal Endothelium - MD, Khalid Alarfaj; Al Osaily, Abdullah; Magliyah, Moustafa (Journal of Cells, 2017)
Introduction: Around half of world blindness and fifth of visual impairment are caused by cataract. Treatment of cataract and refractive errors correction improve 73.6% of blindness. Preservation of the Anterior chamber and corneal endothelium are very important aims during cataract surgery. Methodology: This prospective, observational study was done at King Fahd Hospital of the University (KFUH), Alkhobar, Saudi Arabia. After getting the Institutional Review Board (IRB) approval, the study was initiated at KFUH between April 2016 and August 2016. After getting the patients’ informed consents, a thorough assessment was done to each patient prior to surgery. All eyes enrolled in the study have undergone phacoemulsification surgery procedure. For each patient, one month after the phacoemulsification surgery , specular microscopy was performed. The phacodynamic parameters and surgery time were compared with the degree of endothelial cells loss, hexagonality and central corneal thickness. Results: The phacodynamic parameters used during phacoemulsification, namely, power (AVG %), ultrasound time, and elliptical motion showed a strong correlation with the change of endothelial cell density (all P< .001). The length of surgery also showed a positive correlation with the amount of endothelial cell loss ( P < .001). All of these parameters did not significantly affect corneal endothelial hexagonality except elliptical motion. Change in central corneal thickness was very minimal. Conclusion: Endothelial loss was significantly associated with phacoemulsification power, ultrasound time, elliptical motion and length of surgery.